Modeling and simulation of two modes of vibration in MEMS devices based on embedded piezoresistors - Ahmad, F. (IEEE Computer Society, 2014)
Piezoresistive effect is commonly used as transduction mechanism in microelectromechanical systems (MEMS) and Wheatstone bridge as readout circuit. This paper presents modeling and simulation of two modes of vibration in the MEMS device through embedded piezoresistors which are arranged in Wheatstone bridge configuration, modeling is extended up to n branches for wide range of applications in MEMS. The comparative analysis of fully and half differential setups even with one variable resistor with balanced form of the two branch bridge is modeled as well as simulated using Multisim8. The sensitivity of the bridge in fully, half and with one variable resistor configuration is found to be 2 Î¼V/mÎ©, 1 Î¼V/mÎ© and 0.49 Î¼V/mÎ© respectively. It is found that fully differential set up is the most sensitive one. This output is amplifiable by using 1000 gain amplifier. Â© 2014 IEEE.